Combining coaching with family life. A study of female and male elite level coaches in Norway - Sisjord, M. K.; Fasting, K.; Sand, T. S. (Sports Coaching Review, 2023)
The challenges of combining work and family life has been considered a women`s issue, also reflected in research. In recent years, scholars have argued that the work-family interface may also concern male coaches. Therefore, the present study takes both genders into account. We made qualitative interview with 13 women and six men. The findings revealed similarities as well as differences. For women, support from the spouse was decisive for taking on and maintaining the position, whereas men primarily made the decisions on their own. The responsibility for childcare was far more important among the women. The male coaches seemed more traditional, except for two younger men who gave priority to the fatherhood role. The findings are discussed in relation to a multi-level model, where individual choices/practice may be understood in relation to requirements from the organisation of sport as well as gender roles in the society at large.